A new filling technique with vital micrograft from adipose tissue: a Lipo-Stem-Exos method. A case report - Svolacchia, Fabiano; svolacchia, lorenzo (Aesthetic Medicine, 2025)
Aim: Through this clinical case report, we have demonstrated that the periocular area can be effectively corrected using a single filling session with vital micrografts derived from microfiltrated, fragmented adipose tissue. Over time, vital micrografts have allowed us to maintain a high correction capacity. The technique that we have defined Lipo-Stem-Exos has allowed us to obtain an excellent correction of the volume and the improvement of the Dark Circle, improving the general appearance of the gaze with excellent patient compliance. Background: The eyelid tissue is very thin and during aging, in addition to the loss of elasticity, the eye can experience a depression due to a decrease in periocular volumes with an exposure of the bones that make up the anatomical area and a deficit in the tear trough area. This phenomenon appears to be physiological in all individuals; however, in some cases, it may constitute a genuine cosmetic concern. Method: We subjected a patient to a nasolacrimal sulcus filling treatment with a technique that we defined Lipo-Stem-Exos. After the collection of adipose tissue, we fragmented it and selected viable micrografts with a size between 20 and 40 microns. Filtration of adipose tissue through 20–40 µm filters enabled the isolation of tissue progenitor cells from the side population under hypoxic conditions, while effectively excluding inflammatory contaminants. Results: With this technique we observed and reported excellent long-lasting results. The Lipo-Stem-Exos technique took us about 45 minutes with complete compliance from the patient. Conclusion: We observed the improvement of the periocular area with a clinical maintenance of the results even beyond 240 days from the session. These results suggest that micrografts extracted at 20–40 µm under hypoxic conditions retain viability and contribute to the improvement of the treated anatomical area.